99mTc-MDM Brain SPECT for the Detection of Recurrent/Remnant Glioma—Comparison With ceMRI and 18F-FLT PET Imaging. (October 2015) - Singh, Baljinder; Kumar, Narendra; Sharma, Sarika; Watts, Ankit; Hazari, Puja P.; Rani, Nisha; Vyas, Sameer; Anish, Bhattacharya; Mishra, Anil K.
<x xml:space="preserve">Abstract</x> Purpose To evaluate the diagnostic use of an indigenously developed single vial ready to label (with 99mTc) kit preparation of bis-methionine-DTPA (99mTc-MDM) for the detection of recurrent/residual glioma. Materials and Methods We prospectively studied 32 patients (21 male and 11 female subjects aged 43.0±16.0 years) with clinical suspicion of postoperative recurrent/residual glioma. After radical radiotherapy (54.0–60.0 Gy) with or without concurrent temozolomide as indicated, 99mTc-MDM SPECT and ceMRI of the brain was performed in all the patients and 18F-FLT-PET imaging in 16 of 32 patients. Results MDM SPECT and ceMRI findings were concordant in 28 patients (15 positive and 13 negative). The findings were discordant in the remaining 5 patients, with positive ceMRI and negative MDM-SPECT in 2 patients and negative ceMRI and positive MDM-SPECT in 3 patients. 99mTc-MDM-SPECT, 18F-FLT PET, and ceMRI scan findings were positive in 9 of 16 and negative in 5 of 16 patients. In the remaining 2 of 16 patients, both 18F-FLT-PET and 99mTc-MDM-SPECT were positive, but ceMRI was negative. Sensitivity, specificity, PPV, NPV, and DA of 99mTc-MDM-SPECT for diagnosing recurrent/residual glioma were 88.24%, 81.25%, 83.3%, 86.7%, and 84.8%, respectively. Conclusions The diagnostic accuracy of 99mTc-bis-methionine (MDM)–SPECT imaging was comparable with that of ceMRI and 18F-FLT-PET and may be useful in the management of glioma patients in the postsurgical follow-up period. This imaging technique may be of special interest in peripheral hospitals/developing countries lacking access to expensive PET/cyclotron technology. However, comparison with the existing "gold standard" PET tracers, especially with C-11-methionine-PET imaging and histopathological correlation, is warranted in a large cohort of glioma patients through multicentric studies.